Star ledger : poems - Hull, Lynda, 1954-1994 (Edwin Ford Piper poetry award., 1991)
N this dark but finally redemptive group of poems, the tawdry and the exquisite must coexist: Star Ledger may evoke images of the celestial, but it is also the name of the Newark morning newspaper. Such ironies continually inform Hull's poetry, which is tough and uncompromising but richly veined with a musicality and a lyrical texture that recall earlier epics of the American city such as The Bridge and Paterson.